Serum Ferritin: A Biomarker of Disease Activity in Lupus Nephritis - Kripasindhu Gantait; Akhsaya Elango (Bengal Physician Journal)
Background: Lupus nephritis being the prime etiology of mortality in SLE patients not only alters the course of the disease but also causes exacerbation. So in search for a feasible and accessible biomarker, this study aims to determine the importance of serum ferritin as a surrogate of disease activity in lupus nephritis patients. Materials and methods: Number of SLE patients with and without lupus nephritis is 20 each; diagnosis was made based on SLICC criteria, enrolled in our study. They are subjected to SLEDAI-2k and rSLEDAI scores. Based on rSLEDAI score, SLE patients were categorized into group I, 20 SLE patients with lupus nephritis, and group II, 20 SLE patients without nephritis. Serum levels of ferritin were assessed by chemiluminescent immunoassay (CLIA). Biochemical and immunological tests were done, and the results were analyzed and correlated. Results: Group I exhibited higher but not statistically significant serum ferritin levels compared to group II (p = 0.07). Ferritin levels were also observed to have significant positive correlation with rSLEDAI scores (p <0.01, r = 0.6), SLEDAI scores (p <0.001, r = 0.7), and anti-ds DNA antibody levels (p = 0.013, r = 0.4). Conclusion: Serum ferritin is a promising, widely available and useful biomarker of disease activity in lupus nephritis.